Analysis of Sea Surface Temperature Using Terra Modis Satellite Imagery 2021 Case Study: Ujungpangkah Coastal Gresik - Siti Zainab; Hendrata Wibisana; Anna Rumintang Nauli (Future Science, 2021)
Sea Surface Temperature (SST) is one of the parameters used to measure water quality. Measurement of Sea Surface Temperature (SST) is based on water and ultimately affects the photosynthesis process in the waters. Too much Sea Surface Temperature (SST) can also reduce the availability of dissolved oxygen in the water. Based on the nature of the data which is composite data and ready to use, the SST data requires a geometric correction step. This study aims to analyze Sea Surface Temperature Using the Terra Modis Satellite Imagery Case Study on the coast of Ujungpangkah Gresik. The equipment needed in this activity is a unit of computer equipment and Seadas 4.7.3 software. Remote sensing is very appropriate to be used as a solution to analyze the Coastal Sea Surface Temperature (SST) Ujungpangkah, Fast, cheap and efficient use of image data has been proven in this activity. The results obtained the distribution of sea surface temperature (SST) in the entire coastal area of Ujungpangkah, Gresik Regency. Identification results show a range between 29.18 o C - 35.58 o C. Algorithm model of sea surface temperature (SST) Ujungpangkah coastal area, Gresik Regency y = 543.31x + 29.827 and the degree of determination R² = 0.3911 obtained from the wavelength/reflection Rrs_667. Hypothesis test re- results, the t-test gives the results t stat / t count < critical t / t table or 0.000499432 < 0.499803359 means: that the inside temperature is the same as the 2021 satellite image temperature. In other words, there is no difference between the inside temperature and temperature satellite image 2021.